Implementation of the Hadith on the Prohibition of Begging in the Holy Tower: A Social and Religious Review - Atulwafiyah, Ati; Friyadi, Arif; Masuwd, Mowafg (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
Beggars or individuals who seek to earn money without making an effort to work are often seen as symbols of social issues, which are called social pathologies.  Because this clearly violates the norms of goodness and harms many people, one of the factors is poverty that has not been overcome. This research aims to find out the hadith law about begging, its contents, and its implications for begging mental coping. This type of research is qualitative descriptive research, and uses two types of data, namely primary and secondary. The primary data source is obtained from interviews while secondary data sources are obtained from literature studies, literature, books, or journal analysis studies that are relevant to the topic discussed. The results of this study show that in Islamic sharia begging is a highly prohibited act. Especially if it is done by deceiving others and pretending to be weak, but people are allowed to beg under certain circumstances. The implementation of the prohibition of asking in the Holy Tower needs to be seen from two sides, namely the person who asks and the person who gives, while still paying attention to the manners and rules in the Kudus Regional Regulation. In this research article, it is hoped that it can provide a deep understanding to beggars about the prohibition of begging, as well as its implementation on mental overcoming of begging.